The political economy of taxation and tax reform in developing countries - Jonathan Di John (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Taxation provides one of the principal lenses in measuring state capacity, state formation and power relations in a society. This paper critically examines three main approaches (economic, administrative and political economy) to understanding taxation. It also examines differences in tax composition across middle-income developing regions and finds that Latin American economies tax upper income groups much less than in East Asia and Eastern Europe, and explores the political economy and policy implications of these differences. The paper also examines issues of tax reform in low income/post-war economies and explores the problem that capital flight poses for less developed countries. – taxation ; tax reform ; political economy ; state capacity ; developing countries
Keywords: E62; H20; H24; O20; 330; Steuer; Steuerreform; Entwicklungsländer